2019
DOI: 10.7150/thno.33688
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy impairment contributes to PBDE-47-induced developmental neurotoxicity and its relationship with apoptosis

Abstract: Apoptosis is involved in 2,2',4,4'- tetrabromodiphenyl ether (PBDE-47)-induced developmental neurotoxicity. However, little is known about the role of autophagy, especially its relationship with apoptosis underlying such neurotoxic process. Methods : Using female Sprague-Dawley rats exposed to low-dose PBDE-47 (0.1, 1.0 and 10 mg/kg/day) from pre-pregnancy until weaning of offspring to mimic human exposure, we investigated the effects of PBDE-47 on autophagy and apoptosis in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 44 publications
(50 reference statements)
4
21
0
Order By: Relevance
“…Since cytoprotective autophagy occurred prior to apoptosis [36], apoptosis did not affect cytoprotective autophagy. The relationship between lethal autophagy and apoptosis induced by 2,2 ,4,4 -tetrabromodiphenyl ether and andrographolide analogue in neuroendocrine pheochromocytoma PC12 cells and human leukemic U937 cells, respectively, was similar to our findings: autophagy inhibition disrupted apoptosis, and apoptosis impairment facilitates autophagy [37,38]. In addition, autophagy induced by fucoxanthin in SGC-7901 cells elevated apoptosis but was unaffected by apoptosis [36].…”
Section: Discussionsupporting
confidence: 88%
“…Since cytoprotective autophagy occurred prior to apoptosis [36], apoptosis did not affect cytoprotective autophagy. The relationship between lethal autophagy and apoptosis induced by 2,2 ,4,4 -tetrabromodiphenyl ether and andrographolide analogue in neuroendocrine pheochromocytoma PC12 cells and human leukemic U937 cells, respectively, was similar to our findings: autophagy inhibition disrupted apoptosis, and apoptosis impairment facilitates autophagy [37,38]. In addition, autophagy induced by fucoxanthin in SGC-7901 cells elevated apoptosis but was unaffected by apoptosis [36].…”
Section: Discussionsupporting
confidence: 88%
“…As support, previous research has shown neuromotor behavioral impairments in open field test in C57BL/6 mice following single exposure to PBDE‐47 (1, 10, or 30 mg/kg) on PND 10 20 . Additionally, these findings are in line with our earlier report that perinatal PBDE‐47 exposure from before pregnancy to PND 21 at comparable dosage (1.0 and 10 mg/kg/day) produced poor performance in the MWM test 21 . More importantly, these data are in accord with the epidemiological research that PBDEs exposure during developmental periods is related to delayed mental and motor development, as well as declined mental ability and attention deficit in the preschool stage 22,23 .…”
Section: Discussionsupporting
confidence: 91%
“…20 Additionally, these findings are in line with our earlier report that perinatal PBDE-47 exposure from before pregnancy to PND 21 at comparable dosage (1.0 and 10 mg/kg/day) produced poor performance in the MWM test. 21 More importantly, these data are in accord with the epidemiological research that PBDEs exposure during developmental periods is related to delayed mental and motor development, as well as declined mental ability and attention deficit in the preschool stage. 22,23 Overall, our findings provide additional evidence that PBDEs are developmental neurotoxicants.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Changes in the endoplasmic reticulum and mitochondria are induced by external pressure, such as reactive oxygen species, and autophagy and apoptosis are subsequently induced. The similar or opposite functions of autophagy and apoptosis reveal the possible structural relationship underlying autophagy 15,16 . Mammalian target of rapamycin (mTOR) is a serine/threonine protein kinase that plays an important role in promoting metabolism and participates in apoptosis, autophagy and other physiological processes 17 .…”
Section: Introductionmentioning
confidence: 99%